Effect of soil moisture contents on thermal performance of earth-air-pipe heat exchanger for winter heating in arid climate: In situ measurement. (January 2019) - Kumar Agrawal, Kamal; Yadav, Tejpal; Misra, Rohit; Das Agrawal, Ghanshyam
Highlights: Fabrication of a unique sub-soil water trickling system (SWTS) integrated with EAPHE system. Three soil moisture content values viz. 5%, 10%, and 15% have been considered for wet EAPHE system. Investigation of the effect of soil moisture variation on thermal performance of EAPHE system. Comparison of thermal performance of dry and wet EAPHE system for winter heating. Estimation of heat transfer rate, COP and knee point position for dry and wet EAPHE systems. Abstract: Earth-air-pipe heat exchanger (EAPHE) system is a passive system but requires long pipes for heat transfer and its performance also gets deteriorated during continuous operation. In this study, the moisture content of sub-soil is increased in the close vicinity of EAPHE pipe and its influence on thermal performance and pipe length requisite for certain temperature rise in winter season have been determined. The system comprises of two identical set-ups of EAPHE system buried at a depth of 3.7 m (one for dry soil, other for wet soil). A unique water impregnation system is presented to maintain different soil moisture content levels in the close vicinity of EAPHE pipe. The knee point for dry EAPHE system is obtained at a pipe length of 40 m from inlet section while in wet EAPHE system knee point is obtained at 28 m, 27 m and 26 m with 5%, 10%, and 15% soil moisture levels respectively, after 12 h of continuous operation. The average heat transfer rate and coefficient of performance increase up to 26.0% and 26.1% respectively, for 15% moisture content at 30 m length of EAPHE pipe as compared to dry system.